2018
DOI: 10.17219/dmp/80863
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent peripheral ossifying fibroma: Case report

Abstract: Most of the reactive lesions in the oral cavity arise from gingiva. Fibroma, focal fibrous hyperplasia, pyogenic granuloma, and peripheral ossifying fibroma are the commonly encountered lesions of gingiva. Peripheral ossifying fibroma (POF) frequently arises from the peripheral tissues like gingiva. It is commonly found in females, mostly in the anterior of the molar region. POF is predicted to arise from the cells of periodontal ligament due to close proximity of gingiva to periodontal ligament. Its exact ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
9
0
4
Order By: Relevance
“…Clinically, the lesions have some distinctions: a POF is generally firm, pale pink to dark red, while a PG has a soft consistency, ranging from dark red to reddish purple, with a tendency to bleed easily [6,7]. As reported, the PG lesion had mixed color and bleeding aspect, while the POF was pink and not bleeding.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Clinically, the lesions have some distinctions: a POF is generally firm, pale pink to dark red, while a PG has a soft consistency, ranging from dark red to reddish purple, with a tendency to bleed easily [6,7]. As reported, the PG lesion had mixed color and bleeding aspect, while the POF was pink and not bleeding.…”
Section: Discussionmentioning
confidence: 77%
“…Histopathologically, the diagnosis of POF includes criteria such as the presence of fibrous connective tissue with variable fibroblast, myofibroblast and collagen content, scarce to abundant endothelial proliferation, and mineralized material. These mineralized components vary from 23-75% and can be of three types: bone, dystrophic calcifications, or cementum [7,8]. A study demonstrated the presence of oxitan fibers around the mineralized components of the POF and a larger area occupied by the connective tissue stroma in relation to the mineralized components when compared to other fibro-bone lesions, in addition to a higher collagen density [9].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically reactive lesions presented as sessile lesions (51%) or peduncle lesions (49%). Lesions were more frequent in females, 99 cases, (63.9%) and less frequent in males, 56 cases, (36.1%) [6]. In another study, Babu et al [8] found the medium size of the reactive lesions ranged between about 0.5-1cm.…”
Section: Discussionmentioning
confidence: 97%
“…Reactive lesions are relatively common in the oral cavity due to the frequency with which the mucous membranes undergo trauma. They often also arise due to bacterial plaque, tartar, and the presence of foreign bodies such as prostheses and orthodontic appliances [6]. Most reactive lesions in the oral cavity involve the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…However, the word "cementifying ossifying fibroma" was changed to ossifying fibroma in the current classification in 2005. 1,7,8 The source of Ossifying Fibroma is believed to be the periodontal membrane. Few OFs comprise predominantly cementum-like calcifications and the rest show just bony material, but a combination of the two categories of calcification is frequently seen in a solitary lesion.…”
Section: Discussionmentioning
confidence: 99%